2008
DOI: 10.1002/cb.241
|View full text |Cite
|
Sign up to set email alerts
|

Consuming the authentic Gettysburg: How a tourist landscape becomes an authentic experience

Abstract: While authenticity pervades everyday consumption in museums, restaurants, theme parks, gift shops, and heritage attractions, among other commercial milieus, academic work on the concept of authenticity remains vague both in terms of its definition and its marketing relevance. In this study, we unpack the concept of authenticity in a Civil War battlefield and we provide insight as to its theoretical relevance for consumption. Our findings elucidate the distinction between authenticity as a product feature and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(69 citation statements)
references
References 33 publications
1
62
0
2
Order By: Relevance
“…Chronis and Hampton 2008;Fyhri 2009;Chrenka and Ira 2011;Kulczyk 2013;Xiaobo 2010). However some of the authors did define the term »tourist landscape« in their works.…”
Section: Tourist Landscape In the Literaturementioning
confidence: 99%
“…Chronis and Hampton 2008;Fyhri 2009;Chrenka and Ira 2011;Kulczyk 2013;Xiaobo 2010). However some of the authors did define the term »tourist landscape« in their works.…”
Section: Tourist Landscape In the Literaturementioning
confidence: 99%
“…In the existing literature, only a few studies could be identified which examined perceived authenticity in a tourism context, but these studies have focused on arts and crafts (Chang, Wall, & Chang, 2008;Revilla & Dodd, 2003), historic parks (Chronis & Hampton, 2006;Chronis & Hampton, 2008), heritage sites (Kolar & Zabkar, 2007;Kolar & Zabkar, 2010) and festival events (Chhabra, Healy, & Sills, 2003). The importance of authenticity has been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Floristic data shows that there should effort to increase tropical species number, minimize species beyond the tropical area, and eradicate potential invasive plants species. The authentic eco-accommodation in a rural area ideally should be able to present the authentic landscapes [24,25]. Therefore, increasing and strengthening tropical images through the introduction and preservation of native tropical countries is important.…”
Section: Consequences For Rural Tourism Area Development and Conservamentioning
confidence: 99%